If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -6p + 7p = -9 Combine like terms: -6p + 7p = 1p -10 + 1p = -9 Solving -10 + 1p = -9 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 1p = -9 + 10 Combine like terms: -10 + 10 = 0 0 + 1p = -9 + 10 1p = -9 + 10 Combine like terms: -9 + 10 = 1 1p = 1 Divide each side by '1'. p = 1 Simplifying p = 1
| -21x-63=-126 | | 3x/4x-5/6=2x/3x | | 8s-4-7s=2-1 | | -0.53k=3.498 | | 16t^2-96t-4=144 | | 3x^2+18x=8 | | 3x(2x+10)=-24 | | m^2+(m-6)m= | | 12x+2=13x+9 | | 4r+3=r+27 | | 4x-1=4+4x+3 | | 23-3x=50 | | 2(w+2)=-6(2w-3)+6w | | 1x/4x+1/2=1x/4x-1/2 | | 0=70 | | 5x-52+2x=2-9x+10 | | 2(a-4)=4a-2(a+4) | | 5+5x-7x=3 | | 6x-25=25-9x | | 6x+3x=x+16 | | -10y+18=3(3x+7) | | 6+5x-7x=3 | | 7y-7+2(4y+5)=-3(y+1) | | 16t^2-96t-4=0 | | y=-11+2 | | 5(k+2)=12+4(2k-1) | | (180)3= | | (6y+14)=940 | | 6x+5=8x+3 | | 6x+5=8x+4 | | -0.7x+0.5+12x=0.5x+0.8 | | y=-11-1 |